Intercomparison of stratospheric HNO3measurements over Antarctica: Ground-based millimeter-wave versus UARS/MLS Version 5 retrievals - Muscari, Giovanni; Santee, Michelle l; de Zafra, Robert L (Journal of Geophysical Research: Atmospheres, 2002)
[1] We present the first intercomparison between the two most comprehensive records of gas‐phase HNO3 profiles in the Antarctic stratosphere, covering the greater part of 1993 and 1995. We compare measurements by the Stony Brook Ground‐Based Millimeter‐wave Spectrometer (GBMS) at the South Pole with Version 5 HNO3 data from the Microwave Limb Sounder (MLS) aboard the Upper Atmospheric Research Satellite. Trajectory tracing was used to select MLS measurements in the 70°–80°S latitude band that sampled air observed by the GBMS during passage over the Pole. When temperatures were near the HNO3 condensation range, additional screening was performed to select MLS measurements that sampled air parcels within 1.5 K of the temperature they experienced over the Pole. Quantitative comparisons are given at 7 different potential temperature levels spanning the range ∼19–30 km. Agreement between the data sets is quite good between 465 and 655 K (∼20–25 km) during a large fraction of the year. Agreement is best during winter and spring, when seasonally averaged differences are generally within 1 ppbv below ∼25 km. At higher altitudes, and during summer and fall, the agreement becomes worse, and GBMS measurements can exceed MLS values by more than 3 ppbv. We provide evidence that differences occurring in the lower stratosphere during fall are due to lack of colocation between the two data sets during a period of strong poleward gradients in HNO3. Remaining discrepancies between GBMS and MLS V5 HNO3 measurements are thought to be due to instrumental or retrieval biases. Published id 4809 5A. Ricerche polari e paleoclima JCR Journal